Beyond Single-User Scheduling: Exploiting Massive MIMO for Concurrent Data Delivery With Minimum Age of Information - Muhammad Fahad Ijaz; Umar Rashid; Omer Waqar (IEEE Open Journal of Vehicular Technology)
With the emergence of real-time applications, modern wireless networks have witnessed the use of Age of Information (AoI) as a critical metric for evaluating the timeliness of data delivery. This paper considers multi-user scheduling, extending beyond traditional single-user scheduling, to exploit the potential of Massive Multiple-Input Multiple-Output (mMIMO) systems for concurrent data delivery over imperfectly known channel state information (CSI). We propose a novel transmission scheduling framework that leverages the spatial multiplexing capabilities of mMIMO to minimize the AoI across multiple users. This results in a joint optimization of multi-user scheduling and power allocation problem for optimum data freshness in a wireless broadcast network. We handle the non-convexity of the resulting problem by utilizing successive convex approximation to specifically reformulate the binary/integer and non-convex constraints of the problem. Extensive simulations demonstrate superior performance of the proposed framework and its solution in terms of AoI compared to existing benchmarks.